Localização de estoques na rede de distribuição de uma empresa do setor siderúrgico - Marcellus Vinagre da Silva (2006)
Location and network design studies have received great attention from specialized literature since the 1960s. For many authors, network design is the main problem of logistic planning, as its decisions deeply affect tactical and operational aspects of a logistic system as a whole. A consistent planning must take into account integrated decisions related to transportation, location of facilities and inventory issues. The classical distribution network models tend to simplify inventory issues, or even neglect them. A common approach to these problems is initially to establish a distribution network and only later implement an inventory policy. This work incorporates inventory issues in a distribution network design allowing the evaluation, through a wider perspective, of the best degree of inventory centralization / descentralization for a product in a established network facility. A nonlinear mixed integer model is proposed to solve a real problem of a national steel company. The total logistic cost and distribution segmentation strategy concepts are explored together with possible economies of scale through inventory centralization. The results obtained with the model implementation showed to be adequate for the resolution of the proposed problem, and the conclusions are in accordance with specialized literature.